The Effect of Zeolite Catalysis Size on Biodiesel Characteristics of Bio-Oil from Tuna Waste - Imron Rosyadi; Haryadi Haryadi; Ni Ketut Caturwati; Syahrul Ivandy (VANOS Journal of Mechanical Engineering Education, 2021)
Indonesia is a country with the third largest tuna production in the world. Fish oil as a fishery product processing waste is a potential material for making biodiesel because it has a high fat content. In this research, biodiesel was made from bio-oil from tuna waste through esterification and transesterification processes at 60°C, stirring speed 360 rpm with a reaction time of 2 hours. The purpose of this study was to determine the levels of Free Fatty Acid (FFA) contained in bio-oil from tuna waste and to determine the effect of the size of the natural zeolite catalyst in the transesterification process on the characteristics of the biodiesel produced. The variables used were the size of the zeolite catalyst 10 - 20, 30 - 40, 50 - 60, 70 - 80, 100 - 120 mesh. From the research results, it can be concluded that the smaller the zeolite catalyst size, the resulting biodiesel is closer to the biodiesel standard and the size of 100-120 mesh which is very close to the SNI 7182: 2015 biodiesel standard with a density value of 849.6 kg/m3, kinematic viscosity 3,413 cSt, moisture content. 0%, acid number 1.10 mg.KOH /gr, flash point 75 ° C, calorific value 8.240 Cal/gr.